Infrared and Raman spectroscopic study of 4-aminopyrimidine tetracyanonickelate complexes - Akkaya, Yasemin; Akalın, Elif; AKYÜZ, ZEKİ TANIL; AKYÜZ, SEVİM (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2007)
4-Aminopyrimidine tetracyanonickelate, M(4APM)(2)Ni(CN)(4) {where M = Mn, Co, Ni, Zn or Cd; 4APM = 4-aminopyrimidine}, coordination polymer compounds have been prepared for the first time and their FT-IR (400-4000 cm(-1)) and FT-Raman (704000 cm(-1)) spectra are reported. 4APM is coordinated to M(II) through one of the pyrimidine ring nitrogen atoms as a monodentate ligand; the amino group is not involved in the complex formation. Vibrational bands arising from both 4APM and the Ni(CN)(4) group, were assigned. The effect of coordination on 4APM vibrational wavenumbers is analysed by comparison with isostructural compounds. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: aminopyrimidine; Hofmann-type complexes; infrared and Raman spectra; tetracyanonickelate; transition metal; pyrimidine; molecules; pyridine; aminopirimidin; Hofmann-tipi kompleksler; Kızılötesi ve Raman spektrumları; geçiş metali; pirimidin; moleküller; piridin